The Effectiveness of the Implementation of E-Ticket Fines for Traffic Violators in the Seluma Regency Region Based on Law no. 22 of 2009 concerning Road Traffic and Transportation: Efektivitas Penerapan Sanksi Denda E-Tilang bagi Pelanggar Lalu Lintas di Wilayah Kabupaten Seluma Berdasarkan Undang-Undang No. 22 Tahun 2009 tentang Lalu Lintas dan Angkutan Jalan - Dhani, Shelfira Oktilisa; Dasan , Ahmad; Sastra, Hendi (Indonesian Journal of Police Studies, 2021)
The number of traffic violations in Indonesia which continues to increase from year to year makes the Police Traffic Corps in the current of era globalization to innovate to make applications that facilitate the handling of ticket cases. In Seluma Regency in particular the traffic violation rates also continue to increase over time. For this reason, throughout Indonesia on December 6, 2017 launching of an application called E-Tilang was carried out in which the E-Tilang application is expected to be a new breakthrough by the Police, especially Traffic to reduce the number of traffic violations, and also to press the rate of illegal fees committed between violators and parties Police. Although it has only been applied for 2 years, the application of the E-Tilang Fines sanctions can be said to be effective and efficient, especially in the Seluma Regency. E-Tilang has many benefits that are felt by various groups including the community and members of the Police especially Traffic. By using the E-Traffic Ticket application, violations committed by violators do not need to use a lot of paper because they are already registered in the E-Traffic Ticket application, if the violator is dealt with by the E-Traffic system, Traffic violators also no longer need to attend court hearings. The application of the E-Tilang application turned out to also have weaknesses which became an obstacle in the application of the E-Tilang fine in the Seluma District. These constraints and weaknesses include the network used in the E-Tilang Application, which still uses 3G / 4G application network accessibility, which if the signal is available is poor, the service will also be disrupted. Then it was still found in the Seluma District Region that there was a lack of public awareness of compliance with the Law.